Evaluating the implementation of ‘Islamic built environment’ in the context of landscape components in public open spaces in Malaysia - Mohd Isa, Norliza; Zen, Ismawi; Bava Mohidin, Hazrina (American Scientific Publishers, 2017)
The main purpose of this paper is to evaluate the implementation of ‘Islamic built environment’ (IBE) concept in public open spaces in Malaysia. Granting the development of IBE must be the basis in every concept of national development in Malaysia. Thus, this research believes that the adaptation of true Islamic concept is the very crucial in public open spaces that belong to the Malaysian community and for public use, besides being the focus of attraction and tourism assets. This research was conducted based on literatures on framework of indicators of truly Islamic environment. The evaluation was prepared through observation on ten indicators, namely (1) Tolerance, (2) Natural Environment, (3) Social Need and Human Comfort, (4) Religious Identity, (5) Order, (6) Economic, (7) Intellectual and Knowledge, (8) Hygiene, (9) Jannah, and (10) Safety in the selected open public spaces in Malaysia. This research employed a descriptive and survey-based research design rooted in quantitative and qualitative research paradigms. The procedure of research methodology is a combination of reviewing literature, data collection, and data analysis to determine the research finding. For data gathering, this research carried out a site survey for on-site observation confined to the context of landscape components in public open spaces. The findings of this research can benefit and guide Malaysian administrators and professionals in built environment industries to generate a better and more appropriate process of implementing an IBE in Muslim countries, particularly with regard to public open spaces.